Control or change? Developing dialogues between desistance research and public protection practices. (March 2014) - Weaver, Beth
This article aims to scope out some of the implications of desistance research for the community management of high risk offenders. Acknowledging the limited empirical research exploring this interface, this article outlines the evolving evidence base and what this tells us about the process of desistance and what supports it. The evidence as to whether 'high risk offenders' desist and what we know about this process is discussed prior to a consideration of the orientation of current practice approaches which can be located in the community/public protection model. Potential dialogues between desistance research and public protection practices are discussed to explore ensuing implications and opportunities for practice.